The stadium and the city - Bale, John; Moen, Olof (Edinburgh University Press, 2012)
Is the stadium a "prison", a "garden" or a "theatre" and do they contribute economically to the areas where they are built? This book explores the stadium as the principal container of the modern urban crowd as it draws on examples from Europe, North America and China.